Retention of the herpes simplex virus type 1 (HSV-1) UL37 protein on single-stranded DNA columns requires the HSV-1 ICP8 protein. - Shelton, L S (1994)
The UL37 and ICP8 proteins present in herpes simplex virus type 1 (HSV-1)-infected-cell extracts produced at 24 h postinfection coeluted from single-stranded-DNA-cellulose columns. Experiments carried out with the UL37 protein expressed by a vaccinia virus recombinant (V37) revealed that the UL37 protein did not exhibit DNA-binding activity in the absence of other HSV proteins. Analysis of extracts derived from cells coinfected with V37 and an ICP8-expressing vaccinia virus recombinant (V8) and analysis of extracts prepared from cells infected with the HSV-1 ICP8 deletion mutants d21 and n10 revealed that the retention of the UL37 protein on single-stranded DNA columns required a DNA-binding-competent ICP8 protein.